Pharmaceutical and chemical pediatric poisoning in Kuwait: a retrospective survey - Abahussain EA; Ball DE (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Past studies of pediatric poisoning in Kuwait have suggested differences at hospital level which could impact on the implementation of public health interventions. The objective was to compare pediatric poisoning admissions at general hospitals in Kuwait. Methods: Retrospective survey of all pediatric poisoning cases at the six general hospitals from January 2004 to December 2005. Case data were documented using ICD-10 criteria and the poisoning severity score. Aggregated data was also obtained from five private hospitals.Results: 978 children were admitted in public hospitals over 2004 and 2005 (no fatalities) being 1.8% and 1.6% of all pediatric admissions (private hospitals admitted 293 cases). The majority of the poisoning cases came from Jahra hospital (>35%), the median age was 2.3 yrs, 93% of cases were under 6 yrs old and 71% were Kuwaiti. Two thirds of cases involved pharmaceuticals although this varied between hospitals with a tendency for more severe cases with chemical poisoning (p=0.011). Kerosene was an important problem at Jahra hospital (34.7% of chemical exposures). Non-opioid analgesics constituted 22.3% of medication exposures with hormones and drugs affecting the autonomic nervous system also common with some difference in pattern between institutions.Conclusion: Case demographics do not vary significantly between the hospitals but there are differences in the nature of toxic agents to which children are exposed suggesting that preventive and educational programs could be targeted to specific areas for maximal effect particularly with regard to household chemical and kerosene exposures.